Synthesis and self-assembling of hyaluronan grafted with ceramide NP for topical drug delivery - Juhaščik, Martin; Štarmanová, Kateřina; Brandejsová, Martina; Večeřová, Petra; Hermannová, Martina; Exnerová, Andrea; Vagnerová, Hana; Štrympl, Ondřej; Nešporová, Kristina; Kováčik, Andrej; Velebný, Vladimir; Huerta-Ángeles, Gloria (Carbohydrate polymers, 2023)
In this work, amphiphilic hyaluronan was synthesized by grafting succinylated N-oleoyl-phytosphingosine via esters bonds. Succinylated N-oleoyl-phytosphingosine (sCER) was first prepared by esterification of hydroxyl moieties of the ceramide with succinic anhydride. The esterification of hyaluronan was governed by crowding effect. The oligomeric HA-sCER derivatives exhibited a strong self-aggregation as evidenced by a very low critical aggregation concentration (1.9 μg mL-1), higher pyrene binding constant (KB), and the smallest particle size (30 nm) in solution. The self-aggregation properties demonstrated to be a function of the substitution degree and molecular weight of HA. The prepared derivatives were non-cytotoxic towards cell lines NIH-3T3. Nanoparticles prepared using oligomeric HA-sCER derivatives improved the penetration of Nile red dye through the stratum corneum due to their smaller size (≤50 nm). The fluorescence intensity localized at the stratum corneum was higher for oligomeric HA-sCER. A significant inhibition of the pro-inflammatory cytokine interleukin-6 production was observed in vitro in macrophages differentiated from THP-1 cells. These findings showed that HA-sCER constituted a promising active ingredient for cosmetics use.
Keywords: Amphiphilic polysaccharides; Self-assembling; Skin penetration; Ceramides; Hyaluronic Acid; Drug Delivery Systems; IL-6; ceramidy; lékové transportní systémy; kyselina hyaluronová; Hyaluronan; esterifikace; Esterification